BLOG SEBAGAI MEDIA DAKWAH (Studi Kasus Mahasiswa Fakultas Agama Islam Universitas Muhammadiyah Bengkulu) - Siti Misbah (JOISCOM (Journal of Islamic Communication), 2020)
ABSTRACT Blogs are applications that are familiar on the internet. It is called a personal website. In a blog, the visitors that read the article can be noted, and at they can give comment. Bolg is one of the social media that can be used as information media for the community. The formulation of the problem in this study is how the Blog to be as a dakwah (missionary endeavour) media (Case study of Students of Islamic religion Faculty of Muhammadiyah University of Bengkulu). The purpose of this study are: To find out, namely: 1). Blog as a dakwah media for students of the Islamic Faculty of Muhammadiyah University of Bengkulu, 2). To find out the problems of students in functioning the blog as a dakwah media. The method used in this study was qualitative with a qualitative descriptive approach, and the data collection techniques, namely: Observation, Interview, and documentation. Based on the results of the study showed that the students already know the blog as one of the media of dakwah against the community. This dakwah system combined the creativity of the students in word processing and made it an article containing preaching messages and then distributed to the social media blogs with the assist of the internet network. Based on the analysis of the results of the media interview blog is one of the media that can be used for dakwah but until now it has not been utilized properly and only a handful of students of the Islamic Religion Faculty who preach by using blog media. It is because the problems faced by students in conducting dakwah through blogs such as: lack of understanding of how to access blogs, inadequate knowledge, and lack of students’ interest in reading. Keywords: Blog, Media, Da'wah